Review of instrumental texture measurements as phenotypic tool to assess textural diversity of root, tuber and banana food products - (:unkn) unknown (My University, 2024)
Source Agritrop Cirad (https://agritrop.cirad.fr/607434/) * Autres projets (id;sigle;titre): ;RTBfoods project;(FRA) Breeding RTB Products for End User Preferences//
Keywords: African Research